Nonlinear optical phenomena : Generation of the second harmonic in ridge waveguides formed in periodically poled lithium niobate. (28th August 2018) - Dudelev, V V; Akhmatkhanov, A R; Greshnyakov, E D; Abdulrazak, S Kh; Bugrov, V E; Kognovitskaya, E A; Kuchinskii, V I; Shur, V Ya; Sokolovskii, G S
Abstract: Generation of the second harmonic of semiconductor laser radiation in the IR range (980–1140 nm) in ridge waveguides with a large refractive index step, formed in periodically poled nonlinear LiNbO3 crystals, is demonstrated. Ridge waveguides have been prepared by precise cutting using a diamond microsaw. Spectral dependences of the SHG power and intensity distributions in the near field of second harmonic and pump radiations have been measured. The results obtained indicate good prospects of designing tunable laser radiation sources in the visible range due to the SHG in ridge waveguides formed in periodically poled nonlinear crystals under semiconductor laser pumping.